UTILIZATION OF INTERNET OF THINGS (IOT) DEVICES AS MEDIA - Henry Iskandar; Selamat Triono; Hidir Efendi (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2023)
This research aims to design media for remote control systems so that the application requires a combination of hardware and software. Internet of Things (IoT) devices are used as hardware devices to monitor the physical conditions of a working mechanical system. At the same time, the software displays data in digital numeric form, which is controlled remotely using the Android and Windows operating systems. This research consists of 3 stages: 1) analysis of problems and basic needs, 2) product design, and 3) product testing. The results of the basic needs analysis determine that learning in automotive electrical electronics, engineering measurement instrumentation, and automotive control systems must include intelligent automotive materials. The results of the IoT hardware and software designs are connected and work well, resulting in accurate data readings. The product testing results obtained an average value of 85.71%, so the IoT data acquisition media trainer functions well. Utilization of IoT devices as a learning simulation medium in the Industrial Revolution 4.0 era.